The Legal Protection of Patients as a Victim of Medical Malpractice by Physicians on Telemedicine Services - Egun Nofianto (International Journal of Law and Society, 2024)
The development of health services has developed in the last few years and continues to grow to the point of giving rise to telemedicine as a term for electronic services medium between patients and health service providers. The purpose of this research is to find the formal legal truth on the protection rights of a patient who used telemedicine services based on the Indonesian Civil Code, Health Law, and other relevant legal material sources, the study aims to determine the legal certainty of the patient using telemedicine services and legal remedies available to patients injured due to telemedicine malpractice. The research method used is normative or doctrinal and involves relevant approaches such as the statute approach, conceptual approach, theoretical approach, and analytical approach which use various legal material sources including primary and secondary legal material, particularly such as legislation, regulation, various legal theories, legal principles, doctrine, and scientific works of scholars including journals, articles, and practice guides.